Concepções e expectativas parentais sobre o filho com transtorno do espectro autista - Feitosa, Giulliany Gonçalves (2020)
The Autism Spectrum Disorder (ASD) is a disorder of the development that includes issues in the areas of socialization, communication and behaviour. The parents’ conceptions about autism influence how the care and the interactions with the children are performed, reflecting in the children’s development. This research aims to explore the parents’ conceptions and expectations about the children with ASD. The participants of this research are 30 parents of children up to five years old, diagnosed with ASD. The instrument used to gather the data are a form with the children’s and parent’s information and an interview. The data was gathered in two institutions: in a Child Psychosocial Care Center and in a Medical center, both located in Campina Grande, Paraiba. The analyse of the data was lightened by what Bardin proposed, and indicates that the parental conceptions about Autism are centered, specially, in not knowing how to define ASD and in define ASD based on characteristics and behaviours presented by the child. Otherwise, the parental expectations include the wish that the children develop in the areas affected by ASD, especially in the social and language area. Besides that, the parents also grow expectations that the children become independent and can, in the future, furnish their own needs. The results indicate that the parental conceptions and expectations about ASD are complex formed and relate with the family’s socioeconomics and psychosocial status, with the children’s characteristics, with the information received, with the parent’s understanding about the parental role and the strategies in action. The results of this research can help the elaboration of instructional material for the family and also be used as a guideline for the elaboration of strategies of action and orientation of health professionals and families of children with ASD.